Navigating Perspectives: Maritime Transport Development - Insights from Semester 3 Cadets at STIP Jakarta - Mudakir Mudakir; Marudut Bernadtua Simanjuntak (Pendekar : Jurnal Pendidikan Berkarakter, 2024)
This qualitative research delves into the perspectives of 240 Semester 3 cadets at the Maritime Institute Jakarta (STIP Jakarta) on Maritime Transport Development in the Global Scale. Over a span of three semesters, these cadets undergo academic, mental, vocational, and professional preparation for internships in the shipping, cargo, or international delivery industry. The study aims to comprehensively understand their insights on the main opportunities, threats, and challenges in the dynamic landscape of global maritime transport. The findings reveal a collective awareness among cadets of the importance of academic preparedness, emphasizing the need for a seamless transition from theoretical knowledge to practical application. Linguistic proficiency, particularly in English Maritime, emerges as a central theme, highlighting its pivotal role in preparing cadets for international roles. The research illuminates a positive outlook on opportunities within the maritime sector, with cadets expressing enthusiasm for emerging technologies, automation, and sustainable practices. However, realistic concerns are voiced about potential threats such as job market saturation and the impact of automation on traditional roles. These concerns underscore the need for adaptive responses from educational institutions to equip cadets with skills relevant to the evolving industry. Challenges such as language barriers and limited exposure to real-world scenarios are identified, suggesting areas for improvement in maritime education. The implications of the research extend beyond STIP Jakarta, urging a more dynamic and responsive approach to maritime education globally. Recommendations include enhancing experiential learning, continuous language training, and incorporating emerging trends into curricula. The findings and recommendations provide a valuable roadmap for institutions seeking to prepare the next generation of maritime professionals for the complexities of the global maritime industry.